14. Implementasi Rezim Internasional Konvensi Basel Terkait Aliran Ilegal Limbah Elektronik atau Electronic Waste (E-Waste) dari Uni Eropa Ke Cina Tahun 2003-2015 - Retnaningtias, Melani; Windiani, Reni; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Electronic waste illegal flow is an emerging environmental crime due to the developmentof market and technology. This crime mostly caused by strong economic motive andusually take place from developed to developing country. This research focused on theimplementation of Basel Convention as an international environmental regime combatingelectronic waste illegal flow with a case study from the European Union to China in 2003-2015. Basel Convention has been implemented by both parties on August 15, 2002 forChina, and 2003 for the European Union. Although have been ratified and implemented byboth parties, the data shows that electronic waste illegal flows remains occurred. Thisresearch aims to analyze the causative factors of electronic waste illegal flows under BaselConvention. Explanative research is used to explain the correlation between variables toexplicate the causative factors. This research using regime theory with a constructivistapproach as analytical tools. The result indicates that there is a cultural contestation existsas one of the causative factors that explain the aims of Basel Convention can not beachieved. Another result shows that the contribution of epistemic community is not highlysignificant due to another variable that is considered more important, which is economicvariable.